If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 130 = 3x + 2y Solving 130 = 3x + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 130 + -3x = 3x + -3x + 2y Combine like terms: 3x + -3x = 0 130 + -3x = 0 + 2y 130 + -3x = 2y Add '-130' to each side of the equation. 130 + -130 + -3x = -130 + 2y Combine like terms: 130 + -130 = 0 0 + -3x = -130 + 2y -3x = -130 + 2y Divide each side by '-3'. x = 43.33333333 + -0.6666666667y Simplifying x = 43.33333333 + -0.6666666667y
| 5x+1+4=11+9x | | 3m+2m+4n+3n= | | 9/4x=1/16 | | 2/3x=140 | | 1=12x-8 | | 5x+8=6x-18 | | 10/9c=-81 | | P-3.2=7.6 | | 7.3y-5.8=51.9 | | 53-2x=5x-17 | | 15+9n=9-n | | 2(7x+2)=-12 | | 2/3z=1/21 | | 50=5ln(3x+7) | | 84=2*35+2*w | | X(8-1)=18 | | -1=2x-8 | | -x/4-5=-8 | | -15+t=20 | | 4/3m=8/15 | | a/3-7=10 | | 25x+2000=2000 | | -7(2-6x)-4x=23+x | | -2+3=-(x+6) | | 84+36=93 | | 3*x+sqrt(3)=3*sqrt(3) | | 1/10=1/5y | | 2f-3=11f-24 | | -8+6x-10-8x= | | -7(6x+7)=-42x+49 | | (2x-2)*x/2=182 | | 2x+13x=40 |